2012
DOI: 10.1063/1.3701165
|View full text |Cite
|
Sign up to set email alerts
|

Gate-last TiN/HfO2 band edge effective work functions using low-temperature anneals and selective cladding to control interface composition

Abstract: Gate-last TiN/HfO2 band edge effective work functions using low-temperature anneals and selective cladding to control interface composition KAUST Repository

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…There have been a few preliminary theoretical 34 and experimental 40,41 investigations of EWF modulation in the recent past. We have carried out a systematic analysis of the EWF modulation through changes in the stoichiometry at the HfO 2 /TiN interface.…”
Section: Effective Work Function Engineeringmentioning
confidence: 99%
“…There have been a few preliminary theoretical 34 and experimental 40,41 investigations of EWF modulation in the recent past. We have carried out a systematic analysis of the EWF modulation through changes in the stoichiometry at the HfO 2 /TiN interface.…”
Section: Effective Work Function Engineeringmentioning
confidence: 99%
“…While the EWF of atomic layer deposition (ALD)-grown stoichiometric TiN ranges from 4.7 to 4.9 eV, relevant for low V th in p-channel MIS transistor, doping of TiN with low WF metal, e.g., Al, results in lower EWF values in the range 4.1–4.4 eV. Another option is provided by exposure of TiN to nitrogen plasma, which points toward significant impact of the metal stoichiometry. , However, there is an additional factor affecting stoichiometry of TiN at interfaces with oxide insulators: the oxygen “scavenging” from the underlying oxide leads to oxidation of the PVD-grown TiN films on SiO 2 and Al 2 O 3 . , …”
Section: Introductionmentioning
confidence: 99%
“…Solutions for the nMOS EWF in the range of 4.1-4.4 eV can be obtained by doping the TiN film with different materials (such as Al and N). [8][9][10] Literature reports had shown that the addition of Al ions into TiN layer can significantly change the TiN EWF. 8,10 The metal gate EWF shift is related to formation of different dipoles at the interface between metal gate and high-k due Al diffusion.…”
Section: Introductionmentioning
confidence: 99%